2009
DOI: 10.1007/s10704-009-9386-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructure on appearance of near-threshold fatigue fracture in Cr–Mo–V steel

Abstract: Near-threshold fatigue crack growth behavior in 25Cr2NiMo1V steel with different microstructures was investigated by utilizing the load-shedding technique at ambient temperature. Crack surface morphology was observed by SEM with special emphases on the incidence of intergranular fracture and the influence on crack growth rates. Results show that the maximum intergranularity occurs at the K corresponding to the cyclic plastic zone size being equivalent to the prior austenitic grain size. Two types of crack grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…9a, c and e are 28%, 30.6% and 28.6%, respectively. Similar behavior of the facet distribution have been reported by Lal [10], Liaw et al [31] and us [32]. This means that facet feature of fracture surface morphology is related to the changes of transition point in BM.…”
Section: Fracture Surface Morphology Around the Transition Pointsupporting
confidence: 87%
“…9a, c and e are 28%, 30.6% and 28.6%, respectively. Similar behavior of the facet distribution have been reported by Lal [10], Liaw et al [31] and us [32]. This means that facet feature of fracture surface morphology is related to the changes of transition point in BM.…”
Section: Fracture Surface Morphology Around the Transition Pointsupporting
confidence: 87%
“…Unfortunately, the literature on the relationship between the fatigue crack propagation behavior and grain size remains controversial, especially regarding that of alloys with multilevel microstructures. [1][2][3][4][5][6][7][8][9][10] For instance, Kang et al believe that refining grains can improve the fatigue crack propagation resistance of low-carbon martensitic Nomenclature: a, crack length; ASTM, American Society for Testing and Materials; B, thickness of compact tension specimen; C, material constant; CTOD, crack tip opening displacement; d, grain size; da/dN, fatigue crack propagation rate; db, martensitic block size; dl, martensitic lath width; dp, martensitic packet size; E, elastic modulus; EBSD, electron backscattering diffraction; FCG, fatigue crack growth; HAGBs, high-angle boundaries; LAGBs, low-angle boundaries; LSCM, laser-scanning confocal microscopy; m, material constant; N, fatigue cycles number; OICC, oxide-induced crack closure; PICC, plasticity-induced crack closure; RCPZ, cyclic plastic zone size; RICC, roughness-induced crack closure; UTS, ultimate tensile strength; W, width of compact tension specimen; YS, yield strength; ΔK, stress intensity factor; ΔK th , fatigue crack threshold value; ΔP, applied load range; v, Poisson's ratio; σy, yield strength steel because as the frequency of cracks encountered with substructure boundaries increased, the crack growth would be hindered, slowing the crack propagation rate. 1 Guo Ping and Ma et al studied the fatigue crack propagation behavior of the TC4 alloy and found that α lamellae have the strongest influence on the fatigue crack propagation rate in the near-threshold region as well as further refinement of the α lamellae improved the crack growth resistance.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, other researchers find that a coarse microstructure is associated with better fatigue crack propagation resistance. [5][6][7][8][9][10] For example, Ma et al 5 investigated the fatigue crack growth behaviors of coarser-grained and fine-grained high manganese austenitic twin-induced plasticity steels. Their results show that the coarse-grained steel exhibits a higher fatigue crack growth resistance than the finegrained steel in both the near threshold and Paris regimes because of both roughness-induced crack closure (RICC) and plasticity-induced crack closure (PICC).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of an ODA/FGA is known to require at least 10 7 fatigue cycles, under fully reversed loading. Surface residual stresses have been reported to play an important role in the competition between surface and internal crack initiation [13][14][15]. Compressive surface residual stresses were reported to inhibit surface crack initiation when they are stable and thus to favor internal crack initiation.…”
Section: Introductionmentioning
confidence: 99%